Statistical Optimization of Culture Conditions for Enhanced Biomass Yield of Lactobacillus acidophilus CM1 Using Plackett–Burman and Response Surface Methodology - Khushboo Rajput; Amar Yasser Jassim; Ameer Abbas Mohammed; Abdel Rahman Mohammad Said Al-Tawaha; Arun Karnwal; Tabarak Malik (International Journal of Food Science)
This study is aimed at enhancing the biomass yield of Lactobacillus acidophilus CM1 by identifying and optimizing critical growth parameters. Using the Plackett–Burman design (PBD), 11 physical and chemical variables were screened, of which pH, temperature, NaCl concentration, and inoculum size were found to significantly influence cell growth (p<0.05). These statistically significant factors were subsequently optimized using response surface methodology (RSM) with a central composite design (CCD). Optimization led to a 1.45-fold increase in biomass yield, achieving a maximum of 1.948 g/100 mL. ANOVA confirmed model validity with an R2 of 0.9689 and adequate precision of 52.77, indicating a strong predictive capability. The integration of PBD and RSM-CCD proved efficient for minimizing experimental runs while maximizing output, supporting the development of cost-effective cultivation strategies for probiotic production. This approach offers a scalable model for bioprocess optimization in industrial fermentation.